2004
DOI: 10.1111/j.0883-2919.2004.00352.x
|View full text |Cite
|
Sign up to set email alerts
|

Shared morpho‐syntactic features in contact varieties of English: article use

Abstract: :  This paper deals with the use of the definite article the and the indefinite article a/an in various ICE corpora. The claims about article use in the varieties under analysis are reexamined in the light of corpus evidence. Distribution patterns of articles across different text types as well as specific usages are discussed in order to characterize the nature of contact varieties, such as Jamaican English, Irish English or Indian English, as opposed to ENL varieties such as British English or New Zealand En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(30 citation statements)
references
References 20 publications
1
29
0
Order By: Relevance
“…This would not even be possible since there are as yet no clear ideas on how different a variety has to be in order to be classified as 6. Studies in which variety differences have been researched based on corpora include De Klerk (2003); Hundt (1998); Rogers (2002); Sand (2004);Schneider (2004). "different".…”
mentioning
confidence: 99%
“…This would not even be possible since there are as yet no clear ideas on how different a variety has to be in order to be classified as 6. Studies in which variety differences have been researched based on corpora include De Klerk (2003); Hundt (1998); Rogers (2002); Sand (2004);Schneider (2004). "different".…”
mentioning
confidence: 99%
“…My data, therefore, do not lend support to Sand's (2005) study. In a study based on a more limited set of eight nouns, Sand found that contact varieties tended to use singular concord even with nouns such as family, police, and staff, that is, nouns that show divided usage or a clear tendency toward plural concord in BrE, AmE, NZE, and AusE.…”
Section: Corpus Comparability?mentioning
confidence: 63%
“…Linguistic features include multi-word verbs (Schneider 2004), negation of lexical have (Nelson 2004) and article use (Sand 2004). The comparisons are made between inner circle varieties (e.g.…”
Section: Application a Linguistic Studiesmentioning
confidence: 99%